A Survey on Digital Trust: Towards a Validated Definition - Julija Saveljeva; Tatjana Volkova (Digital, 2025)
Digital trust is increasingly crucial for successful interactions in modern digital environments. However, the existing literature lacks a unified definition and a comprehensive understanding of its core factors. This study addresses these gaps by conducting a systematic literature review to explore and synthesise existing definitions of digital trust and identify the fundamental factors that shape it. A total of 86 relevant sources were analysed, revealing that digital trust is typically conceptualised as confidence in people, processes, and technology aimed at ensuring a secure digital environment, with data protection and privacy playing critical roles. Through thematic analysis, “openness” emerged as an additional factor complementing previously established elements of the integrative model of organisational trust, such as ability, benevolence, and integrity. Based on 42 definitions, we developed a new holistic definition of digital trust. The authors evaluated its content validity, confirming its alignment with the essential factors shaping digital trust’s essence. The findings highlight the multidimensional nature of digital trust and offer an operationalised framework for future measurement and application.